Multispecific, Multivalent Antibody‐Based Molecules Engineered on the DART® and TRIDENTTM Platforms. (15th April 2020) - Huang, Ling; Shah, Kalpana; Barat, Bhaswati; Lam, Chia‐Ying K.; Gorlatov, Sergey; Ciccarone, Valentina; Tamura, James; Moore, Paul A.; Diedrich, Gundo
Abstract: Multispecific antibodies bind two or more different antigens and enable new therapeutic applications that cannot be replicated with conventional monoclonal antibodies, such as bridging different cells or bringing soluble proteins in close proximity. The DART and TRIDENT platforms enable the engineering of such antibodies. A DART molecule combines two independent antigen‐binding sites in a stabilized, diabody‐like structure. A DART molecule can be expressed with or without an Fc domain and thus can be tailored to have a long or short half‐life in vivo and to induce or ablate effector function. Linking two DART units or a DART unit and a Fab domain (the latter structure is called TRIDENT format) via an Fc domain creates a monospecific, bispecific, trispecific, or tetraspecific molecule with up to tetravalent targeting of antigens. This article focuses on the design of DART and TRIDENT molecules that target two or three different antigens. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Design and generation of expression plasmids encoding DART and TRIDENT molecules Basic Protocol 2 : Expression of DART and TRIDENT molecules by transient transfection of CHO cells Basic Protocol 3 : Purification of DART and TRIDENT molecules from CHO cell supernatants